Multicentre analysis of the learning curve for laparoscopic liver resection of the posterosuperior segments. Issue 11 (23rd August 2019) - Berardi, G; Aghayan, D; Fretland, Å A; Elberm, H; Cipriani, F; Spagnoli, A; Montalti, R; Ceelen, W P; Aldrighetti, L; Abu Hilal, M; Edwin, B; Troisi, R I
Abstract: Background: Laparoscopic liver resection demands expertise and a long learning curve. Resection of the posterosuperior segments is challenging, and there are no data on the learning curve. The aim of this study was to evaluate the learning curve for laparoscopic resection of the posterosuperior segments. Methods: A cumulative sum (CUSUM) analysis of the difficulty score for resection was undertaken using patient data from four specialized centres. Risk-adjusted CUSUM analysis of duration of operation, blood loss and conversions was performed, adjusting for the difficulty score of the procedures. A receiver operating characteristic (ROC) curve was used to identify the completion of the learning curve. Results: According to the CUSUM analysis of 464 patients, the learning curve showed an initial decrease in the difficulty score followed by an increase and, finally, stabilization. More patients with cirrhosis or previous surgery were operated in the latest phase of the learning curve. A smaller number of wedge resections and a larger number of anatomical resections were performed progressively. Dissection using a Cavitron ultrasonic surgical aspirator and the Pringle manoeuvre were used more frequently with time. Risk-adjusted CUSUM analysis showed a progressive decrease in operating time. Blood loss initially increased slightly, then stabilized and finally decreased over time. A similar trend was found for conversions. The learning curve was estimated to be 40 procedures for wedge and 65 for anatomical resections. Conclusion: The learning curve for laparoscopic liver resection of the posterosuperior segments consists of a stepwise process, during which accurate patient selection is key. Graphical Abstract: The learning curve for laparoscopic liver resection of lesions located in the posterosuperior segments consists of a stepwise process in which patient selection plays the most important role. Stepwise approach sensible